Meta-Analysis of the Role of Varenicline in Smoking Cessation - Lafif, Muhammad Zainul; Murti, Bhisma; Prasetya, Hanung (Indonesian Journal of Medicine, 2021)
Background: Smoking is the leading cause of premature death in both developed and developing countries. Smoking cessation efforts can be classified into pharmacological and therapeutic strategies. Varencline is the latest discovery for pharmacological therapy for smoking cessation programs. This study aims to determine the role of varenicline on smoking cessation efforts.Subjects and Method: This was a systematic review and meta-analysis conducted using PRISMA flow diagrams. Search articles through journal databases including: Google Scholar, MEDLINE/ PubMed, Science Direct, Scopus, and Spinger Link by selecting articles published in 2011-2021. The keywords used are “varenicline” OR “pharmacotherapy” AND tobacco OR smoke OR smoked OR smoker AND “smoking cessation”. The research instrument used to assess smoking cessation efforts was the Fagerstrom Test for Nicotine Dependence (FTND). The inclusion criteria were full paper articles with Randomized Controlled Trial (RCT) research methods, the relationship measure used was Mean SD, the intervention given was varenicline, the research subjects were adult smokers who wanted to quit smoking. Eligible articles were analyzed using the Revman 5.3 application.Results: Meta-analysis of 9 articles showed results (SMD -0.11; 95% CI = -0.17 to -0.05; p<0.001).Conclusion: Varenicline has a statistically significant effect in reducing the frequency of smoking per day.Keywords: Varenicline, smoking cessation, quitting smokingCorrespondence: Muhamad Zainul Lafif. Masters Program in Public Health. Universitas Sebelas Maret, Jl.Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: zainullafif@gmail.com. Mobile: 082137179433.Indonesian Journal of Medicine (2021), 06(04): 354-363https://doi.org/10.26911/theijmed.2021.06.04.01